Identification of a novel TNRC18‐RARA fusion in acute promyelocytic leukemia lacking t(15;17)(q24;q12)/PML‐RARA. Issue 2 (11th January 2021) - Wang, Zheng; Wen, Lijun; Zhang, Ling; Xu, Xiaoyu; Chen, Xiaoqian; Yao, Li; Wang, Man; Shen, Zhen; Mo, Guangquan; Wang, Yao; Zhao, Dewan; Cai, Wei; et al.
Abstract: Acute promyelocytic leukemia (APL) is a unique disease entity in acute myeloid leukemia, characterized by PML‐RARA fusion gene, which is generated by chromosomal translocation t(15;17)(q24;q21). We identified TNRC18‐RARA as novel RARA fusion in resembling APL. Our study highlights the importance of combining multiple molecular techniques to characterize and optimally manage APL lacking classic t(15;17)(q24;q12)/ PML‐RARA fusion.